Discovery of 5-aryl-1, 3-dihydro-2H-imidazo[4, 5-b]pyridin-2-ones as positive allosteric modulators of metabotropic glutamate subtype-2 (mGlu2) receptors with efficacy in a preclinical model of psychosis. Issue 4 (15th February 2016) - Layton, Mark E.; Reif, Alexander J.; Hartingh, Timothy J.; Rodzinak, Kevin; Dudkin, Vadim; Wang, Cheng; Arrington, Ken; Kelly, Michael J.; Garbaccio, Robert M.; O'Brien, Julie A.; Magliaro, Brian C.; Uslaner, Jason M.; et al.
Graphical abstract: Abstract: Optimization of a benzimidazolone template for potency and physical properties revealed 5-aryl-1, 3-dihydro-2 H -imidazo[4, 5- b ]pyridin-2-ones as a key template on which to develop a new series of mGlu2 positive allosteric modulators (PAMs). Systematic investigation of aryl-SAR led to the identification of compound27 as a potent and highly selective mGlu2 PAM with sufficient pharmacokinetics to advance to preclinical models of psychosis. Gratifyingly, compound27 showed full efficacy in the PCP- and MK-801-induced hyperlocomotion assay in rats at CSF concentrations consistent with mGlu2 PAM potency.